On-Grid PV Performance in Various Irradiation Conditions, Types, and Load Power - Alamsyah Achmad; Usman Usman; Ahmad Rizal Sultan; Ahmad Rosyid Idris; Andarini Asri; Fahmi Ryadin (PROtek : Jurnal Ilmiah Teknik Elektro, 2023)
There are several types of photovoltaic system configurations, one of which is the on-grid PV system. This system is simple compared to other systems. Because there are two different energy sources that can supply the load either together or separately, an analysis of how the irradiation affects the electrical parameters on the load side or the grid itself is required. The goal of this research is to examine the performance of on-grid PV under various irradiation variation, type, and load power to power factor, grid frequency, and load conditions. To measure the performance of on-grid PV, parameter calculations are carried out in the form of PV efficiency, final yield, reference yield, and performance ratio, and the results of measurements of power factor, grid frequency, and load are observed due to variations in irradiation, type, and load power. The results show that the performance of on-grid PV is good; low irradiation can result in a decrease in the grid power factor, while the grid and load frequencies are in normal conditions for various variations of irradiation, type, and load power.